2016
DOI: 10.18632/oncotarget.9026
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fibrosis in myelodysplastic syndromes: a prospective evaluation including mutational analysis

Abstract: The biological and molecular events that underlie bone marrow fibrosis in patients with myelodysplastic syndromes are poorly understood, and its prognostic role in the era of the Revised International Prognostic Scoring System (IPSS-R) is not yet fully determined. We have evaluated the clinical and biological events that underlie bone marrow fibrotic changes, as well as its prognostic role, in a well-characterized prospective patient cohort (n=77) of primary MDS patients. The degree of marrow fibrosis was link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 45 publications
(50 reference statements)
0
30
2
2
Order By: Relevance
“…Elevated LDH is a disease feature previously reported to be associated with poor survival in MDS (Greenberg et al , ). A negative prognostic value of bone marrow fibrosis has been observed in some (van Spronsen et al , ; Ramos et al , ) but not in all studies (Greenberg et al , ). In unadjusted analyses, patients with fibrosis ≥ grade 2 had a shorter median OS in our study but not in adjusted analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Elevated LDH is a disease feature previously reported to be associated with poor survival in MDS (Greenberg et al , ). A negative prognostic value of bone marrow fibrosis has been observed in some (van Spronsen et al , ; Ramos et al , ) but not in all studies (Greenberg et al , ). In unadjusted analyses, patients with fibrosis ≥ grade 2 had a shorter median OS in our study but not in adjusted analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Both TET2 mutations have previously been reported in myelodysplastic syndrome. 34 Finally, in 2 patients (65 and 92), complex and distinct changes in clonal structures occurred from diagnosis to pre-allo-SCT (presumably reflecting selection by IC or possibly de novo mutation), and from pre-allo-SCT to relapse ( Figure 4C; summarized in Figure 4D and supplemental Tables 4 and 5). …”
Section: Genetic Characterization Of Disease At Relapse In Comparisonmentioning
confidence: 94%
“…Similarly, Ramos et al (2016) showed an association between bone marrow fibrosis and TP53 protein accumulation. It is possible that there is a biological interaction between mutations in the TP53 gene and bone marrow fibrosis; however, these mechanisms have yet to be elucidated.…”
Section: Figmentioning
confidence: 86%
“…Bone marrow fibrosis is a histological finding in approximately 10-20% of patients with de novo MDS; however, MDS with fibrosis is not yet recognized as a distinct entity and its prognostic role is still under debate (Ramos et al, 2016).…”
mentioning
confidence: 99%